Legitimasi Fatwa AI dalam Legislasi Syariah Pada Sistem Hukum Modern - Muhammad Aqsho Che Athoriq R; Rangga Mahesa; Kurniati K (Media Hukum Indonesia (MHI), 2026)
The rapid development of Artificial Intelligence (AI) has created new opportunities to support the process of issuing fatwas by enabling faster and more systematic analysis of Islamic legal sources. However, the involvement of AI in the process of istinb?? al-a?k?m raises concerns regarding the legitimacy of AI-assisted fatwas, particularly in relation to authority, accountability, and compliance with Sharia principles within modern legal systems. This study aims to examine the legitimacy of AI-assisted fatwas in Sharia legislation within modern legal systems and to formulate a regulatory framework that balances technological innovation with the authority of Islamic law. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The findings reveal that AI does not possess the legal or religious authority to issue fatwas independently but should function solely as a supporting instrument in the process of ijtih?d under the supervision of qualified muftis or authorized fatwa institutions. Therefore, the legitimacy of AI-assisted fatwas can only be ensured through regulations that clearly define the scope of AI utilization, establish verification mechanisms by religious authorities, and uphold the principles of algorithmic transparency and accountability. This study recommends the development of a regulatory framework and ethical guidelines integrating the principles of maq??id al-shar??ah with AI governance, while encouraging further research on the implementation of AI-assisted fatwas across different legal systems and fatwa institutions.